The Relationship Between Protein and Iron Intake and Hemoglobin Levels of Students, Class of 2019, Faculty of Medicine, Christian University of Indonesia - Mega Trescylia Oktavia Hukom; Rahayu Yekti (Pro-Life, 2026)
Adequate nutrition is essential for red blood cell formation and maintaining normal hemoglobin levels. Deficiencies in essential nutrients can disrupt hemoglobin synthesis and oxygen transport throughout the body. Protein and iron are among the most important nutrients involved in these processes. Protein contributes to cell formation and tissue development, while iron is a vital component of hemoglobin. Low hemoglobin levels can lead to anemia, which can reduce physical performance and productivity. This study aimed to analyze the relationship between protein and iron intake and hemoglobin levels among college students. An observational, analytical cross-sectional study was conducted. Sixty participants were selected using purposive sampling. Dietary intake data were collected through questionnaires and analyzed using NutriSurvey software. Hemoglobin concentration was measured using photometry. The relationship between nutrient intake and hemoglobin levels was examined using the Spearman correlation test. The results showed that 66.7% of participants had insufficient protein intake, while 33.3% met the recommended intake. For iron intake, 21.7% of participants had insufficient intake, and 78.3% had sufficient intake. Statistical analysis showed no significant relationship between protein intake and hemoglobin levels, with an r value of 0.082 (p=0.535). Conversely, iron intake was significantly associated with hemoglobin levels with an r value of 0.631 (p=0.000). In conclusion, protein intake was not associated with hemoglobin concentration, while iron intake showed a significant relationship with hemoglobin levels. Therefore, adequate iron consumption can play an important role in maintaining normal hemoglobin status.